2018
DOI: 10.1051/bmdcn/2018080319
|View full text |Cite
|
Sign up to set email alerts
|

Weight loss might be an early clinical feature of undiagnosed human immunodeficiency virus infection in Taiwan

Abstract: Background/Objective: Little research is available on the relationship between weight loss and human immunodeficiency virus (HIV) infection in Taiwan. We hope to evaluate whether weight loss could be an early clinical feature of undiagnosed HIV infection in Taiwan.Methods: We conducted a retrospective population-based cohort study using the database of the Taiwan National Health Insurance (NHI) Program. There were 4748 male subjects aged 1-84 with newly diagnosed weight loss as the weight loss group from 1998-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…On the opposite side of the above results, body weight exhibited a protective effect for elderly inpatients to prevent HAIs. Published studies suggested that weight loss should be added to the list of risk factors for some special infections such as invasive aspergillosis, tuberculosis and other chronic infection [22, 23]. Weight loss reflects a failure of dietary intake to maintain an adequate nutritional status and results in immuno-compromised to be vulnerable to infections.…”
Section: Discussionmentioning
confidence: 99%
“…On the opposite side of the above results, body weight exhibited a protective effect for elderly inpatients to prevent HAIs. Published studies suggested that weight loss should be added to the list of risk factors for some special infections such as invasive aspergillosis, tuberculosis and other chronic infection [22, 23]. Weight loss reflects a failure of dietary intake to maintain an adequate nutritional status and results in immuno-compromised to be vulnerable to infections.…”
Section: Discussionmentioning
confidence: 99%